Pathways to public relations
1 online resource (xxxviii, 354 pages)
Keywords: "Over the centuries, scholars have studied how individuals, institutions and groups have used various rhetorical stances to persuade others to believe in and adopt a course of action. The emergence and establishment of public relations as an identifiable and discrete occupation in the early 20th century led scholars to describe this new iteration of persuasion as a unique, more systematized and technical form of wielding influence. The result was an overemphasis on practice that explained public relations' ascendancy as an evolution and refinement of persuasive communication tactics. This volume responds to such simplistic, largely corporate and American, approaches by expanding the framework for understanding public relations history. It investigates broad, conceptual questions concerning the ways in which public relations rose as a practice and a field within different cultures at different times in history and in different places. With its unique multicultural emphasis, it helps shift the paradigm of public relations history away from traditional methodologies and assumptions. Pathways to Public Relations provides a synthesis of a complicated arena that no other edited volume has attempted. With its wide range of historical perspectives and multiple levels of analysis that fully contextualizes public relations, this book showcases a range of cultural and contextual aspects from a diverse range of historians active within the public relations field"--